Proportion of lung adenocarcinoma in female never-smokers has increased dramatically over the past 28 years - Huang, Cuicui; Qu, Xiao; Du, Jiajun (Journal of Thoracic Disease, 2019)
We read with interest the editorial from Zheng et al., and in the article, the authors stated that the incidence of lung cancer has increased in young non-smoking women in China (1). This phenomenon is interesting and has important clinical significance. To verify this increase, we conducted a retrospective review of 8,668 patients who underwent resection for lung cancer from January 1, 1990 to December 31, 2017.